Dr. D.N. Shastri felicitation volume : Indological studies : presented to Dr. Dharmendra Nath Shastri in 85th year of his life by his students, admirers, and friends - Shastri, D. N. (Dharmendra Nath), 1897-; Pal, Keshav Ram (Vimal Prakashan, 1982)
Festschrift honoring Dharmendra Nath Shastri, b. 1897, Indologist; comprises articles on his life and works and Indic studies.